Economic burden of sarcoidosis in a commercially-insured population in the United States. (3rd October 2017) - Rice, J. Bradford; White, Alan; Lopez, Andrea; Conway, Alexandra; Wagh, Aneesha; Nelson, Winnie W.; Philbin, Michael; Wan, George J.
Abstract: Background: Sarcoidosis is a multi-system inflammatory disorder characterized by the presence of non-caseating granulomas in involved organs. Patients with sarcoidosis have a reduced quality-of-life and are at an increased risk for several comorbidities. Little is known about the direct and indirect cost of sarcoidosis following the initial diagnosis. Aims: To provide an estimate of the healthcare resource utilization (HCRU) and costs borne by commercial payers for sarcoidosis patients in the US. Methods: Patients with a first diagnosis of sarcoidosis between January 1, 1998 and March 31, 2015 ("index date") were selected from a de-identified privately-insured administrative claims database. Sarcoidosis patients were required to have continuous health plan enrollment 12 months prior to and following their index dates. Propensity-score (1:1) matching of sarcoidosis patients with non-sarcoidosis controls was carried out based on a logistic regression of baseline characteristics. Burden of HCRU and work loss (disability days and medically-related absenteeism) were compared between the matched groups over the 12-month period following the index date ("outcome period"). Results: A total of 7, 119 sarcoidosis patients who met the selection criteria were matched with a control. Overall, commercial payers incurred $19, 714 in mean total annual healthcare costs per sarcoidosis patient. The principle cost drivers were outpatient visits ($9, 050 2015 USD, 46%) and inpatient admissions ($6, 398, 32%). Relative to controls, sarcoidosis patients had $5, 190 (36%) higher total healthcare costs ($19, 714 vs $14, 524; p  < 0.001). Sarcoidosis patients also had significantly more work loss days (15.9 vs 11.3; p  < 0.001) and work loss costs ($3, 288 vs $2, 527; p  < 0.001) than matched controls. Sarcoidosis imposes an estimated total direct medical cost of $1.3–$8.7 billion to commercial payers, and an indirect cost of $0.2–$1.5 billion to commercial payers in work loss. Conclusions: Sarcoidosis imposes a significant economic burden to payers in the first year following diagnosis.